The New Testament : a historical and theological introduction - Hagner, Donald Alfred (Grand Rapids, MI Baker Academic, 2012)
"This substantial introduction explores the origin and character of the New Testament writings. Donald Hagner deals with the New Testament both historically and theologically, employing the framework of salvation history. He treats the New Testament as a coherent body of texts and stresses the unity of the New Testament without neglecting its variety. Although the volume covers typical questions of introduction--such as author, date, background, and sources--it focuses primarily on understanding the theological content and meaning of the texts. Throughout this capstone work, Hagner delivers balanced conclusions in conversation with classic and current scholarship, making this an essential resource for seminarians, graduate students, and upper-divisional undergraduates for study and lifelong reference. The book includes summary tables, diagrams, maps, and extensive bibliographies"--Publisher description
Introduction and background. Approaching the New Testament as the church's scripture -- The Old Testament as promise and preparation -- The world of the New Testament -- The Gospels : the proclamation of the kingdom. The Gospels as historical and theological documents -- The message of Jesus -- The "historical" Jesus -- The origin and reliability of the gospel tradition -- Form and redaction criticism -- The Synoptic problem -- Q as an entity -- The Gospel according to Mark -- The Gospel according to Matthew --
Includes bibliographical references and indexes
Keywords: Bible. -- Introductions